Next-generation sequencing approach for connecting secondary metabolites to biosynthetic gene clusters in fungi - Cacho, Ralph A.; Tang, Yi; Chooi, Yit-Heng (Frontiers in Microbiology, 2015)
Genomics has revolutionized the research on fungal secondary metabolite biosynthesis. To elucidate the molecular and enzymatic mechanisms underlying the biosynthesis of a specific secondary metabolite compound, the important first step is often to find the genes that responsible for its synthesis. The accessibility to fungal genome sequences allows the bypass of the cumbersome traditional library construction and screening approach. The advance in next-generation sequencing (NGS) technologies have further improved the speed and reduced the cost of microbial genome sequencing in the past few years, which has accelerated the research in this field. Here, we will present an example work flow for identifying the gene cluster encoding the biosynthesis of secondary metabolites of interest using an NGS approach. We will also review the different strategies that can be employed to pinpoint the targeted gene clusters rapidly by giving several examples stemming from our work.